Design Analysis and Development of Inverter Topologies for Industries - Sunita Kumari; Sudhir Y Kumar (IAES Indonesian Section, 2018)
This paper presents the most common inverter topologies and its design, analysis and development schemes. The main objective is to design and compare the three topologies of multilevel inverter for industries. These three topologies are mostly effectively and efficiently for quality improvement of the output voltage waveform of inverter. Photovoltaic (PV) and wind power generation (WPG) i.e. the renewable energy systems are playing a vital role in energy production. But, solar photovoltaic power (PV) has the prospective to develop one of the foremost suppliers to the future electricity supply. Therefore, Low voltage solar PV systems need a high voltage expansion converter for units of grid connection with multilevel inverter. The multilevel inverter topologies are being used in applications of medium and high power such as an active power filter, FACTS devices and a machine current due to their various merits in terms of power supplies low power dissipation, low harmonic distortion in voltage output waveform. Therefore, the simulation of multilevel inverter topologies is done and finalized that cascade multilevel inverter topology is more suitable as compared to other two by using MATLAB/SIMULINK.